Personality traits and entrepreneurial intention: mediating effect of educational support in public higher education / Mazlina Mamat ...[et al.] - Mamat, Mazlina; Abu Bakar, Hatinah; Samat, Muhammad Faizal; Setapa, Mariam (Universiti Teknologi MARA, 2021)
The purpose of this paper was to examine the influence of personality traits (agreeableness, conscientious, neuroticism, openness and extraversion) on entrepreneurial intention and to assess the mediating role of educational support on the relationships between personality traits and entrepreneurial intention. A total of 1000 students at Universiti Teknologi MARA Cawangan Kelantan (UiTMCK) were randomly selected. Questionnaire was distributed to various faculties such as the Faculty of Business & Management, Faculty of Accountancy, Faculty of Computer & Mathematical Science, and Faculty of Information Management and Art & Design. A total of 800 responses were collected and 753 of the responses were useable for the final analysis using the structural equation model partial least square (SEM-PLS 3.0). The findings revealed that agreeableness, conscientious, neuroticism, and extraversion have a significant influence on entrepreneurial intention but openness showed an insignificant influence. Besides, this study also found that educational support did not mediate the relationships between agreeableness, conscientious, neuroticism, openness and extraversion.